1973
DOI: 10.1111/j.1651-2227.1973.tb08088.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pressure‐volume Relationship of the Lung and Position in Healthy Neonates

Abstract: Summary There is no significant difference in the dynamic V/P loops of the lung between supine position with the head in normal median position, and prone position, i.e. when there is no deformation of the upper airways. In both prone and supine position with flexion or rotation of the head, the slope of the V/P loops was decreased and the width of the loops in creased. In pulmonary function tests special attention should therefore be given to the position of the head in relation to the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…R rs does vary inversely with lung volume (26,27), but FRC did not change significantly in this subgroup of patients. A decrease in R L in the prone position was reported by Mendoza and colleagues (11), although most authors have found no change (6)(7)(8)10). To the best of our knowledge this is the first study to measure positional changes in R rs in patients with severe obstructive disease.…”
Section: Changes In Aapo 2 Ratio In All Patients (N ϭ 30 Unless Othermentioning
confidence: 86%
See 2 more Smart Citations
“…R rs does vary inversely with lung volume (26,27), but FRC did not change significantly in this subgroup of patients. A decrease in R L in the prone position was reported by Mendoza and colleagues (11), although most authors have found no change (6)(7)(8)10). To the best of our knowledge this is the first study to measure positional changes in R rs in patients with severe obstructive disease.…”
Section: Changes In Aapo 2 Ratio In All Patients (N ϭ 30 Unless Othermentioning
confidence: 86%
“…Although many authors hypothesize the improvement in oxygenation is due to an increase in functional residual capacity (FRC) (4,5,9) there are no published studies documenting positional changes in FRC in children with severe lung disease. A number of investigators have examined pulmonary mechanics in the prone and supine positions (6)(7)(8)(9)(10)(11). However these studies have largely been carried out in spontaneously breathing neonates (some intubated and some not) with, at worst, mild lung disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there appears to be little evidence that lung volume is position-dependent in the recumbent infant [12], mechanics and respiratory pattern do appear to be position-dependent, especially in the anaesthetized infant or one with respiratory disease [12][13][14][15][16][17][18].…”
Section: Posturementioning
confidence: 99%
“…intensive care (24). The inflation reflex, however, is more cOmInOn in infants with non-compliant lungs (10) and thus may be reduced by the improved lung function associated with prone positioning (23,24). a consequence, prone nursing may have a n adverse effect if reflexes are still an important respiratory control mechanism.…”
Section: The Hering-breuer Reflexes and Sudden Infant Deathmentioning
confidence: 99%